Multi-objective allocation optimization model for water resources from a coal mine in the Inner Mongolia-Shaanxi contiguous area - Hechao MIAO; Shuning DONG; Hao WANG; Yuanyuan YANG; Wei QIAO; Xiaodong WANG; Dongqi WANG; Hongyang FU; Yuting LIU (Meitian dizhi yu kantan)
ObjectiveIn China, as coal resource exploitation shifts gradually from eastern to western regions, coal bases in the western region play an increasingly notable foundational role in the basic energy supply in the national economy. However, due to its fragile ecosystems, the safe, efficient, and green coal exploitation of this region has long been challenged by the contradiction between the prevention and control of water hazards and the conservation of water resources. Therefore, advancing intelligent mine water control technology is identified as a crucial method to address the conflicts between coal mining and mine water in the western region. Additionally, this approach is also an urgent need for the conservation and utilization of water resources in mining areas on the premise of guaranteeing the production safety of coal enterprises.MethodsThe existing technology of mine water allocation faces several issues, including less comprehensive allocation rules based on supply priorities and water quality and insufficient consideration of the special properties of mine water. To overcome these limitations, using surface water, groundwater, mine water, and reclaimed water as water sources, this study developed a multi-objective allocation optimization model considering economic and environmental benefits and equity for water resources in coal mining areas. Based on the newly established water resource allocation rules and in combination with the conditions including water balance, water quality standards, and constraints on water consumption, this study employed the non-dominated sorting genetic algorithm Ⅱ (NSGA-Ⅱ) to determine the monthly allocation schemes for water resources under the base year of current status level in a coal mine within the Inner Mongolia-Shaanxi contiguous area. Moreover, this study assessed the allocation schemes orientated to economic benefits, environmental benefits, and equity, based on the Pareto solution set. This study case validated the effectiveness of the model.Results and ConclusionsThe allocation results proved reasonable, with the average annual utilization rate of mine water determined at about 78.4%. The average monthly utilization rate of mine water was positively correlated with the difference between monthly water supply and demand, with ecological and agricultural water demand acting as significant influential factors. April and August saw the highest (92.2%) and lowest (31.4%) average monthly utilization rates of mine water, respectively. Economy- or environment-orientated schemes are recommended for the two months. For the environment-orientated scheme from January to December, the utilization rate ranges of surface water, groundwater, mine water, and reclaimed water were calculated at 100%, 35.21% to 100.00%, 32.18% to 95.11%, and 82.89% to 100.00%, respectively. The satisfaction rates for domestic, industrial, ecological, and agricultural water ranged from 95.00% to 98.16%, from 97.27% to 109.14%, from 94.35% to 105.05%, and from 81.95% to 108.85%, respectively. The low utilization rate of mine water corresponded to increased utilization rates of other water sources, indicating an unreasonable water supply structure. The results of this study provide a theoretical basis and practical guidance for the scientific management and comprehensive utilization of mine water in mining areas while also offering a reference for the allocation optimization of similar resources.